The Relationship of Self Efficacy towards Improving Quality of Santri Organization in Daar El-Qolam - TAUFIK ABDILLAH SYUKUR; AISHA TARA ATHIRA (Ta'dib: Jurnal Pendidikan Islam, 2019)
In this modern era, for its rapid grown, Pesantren has played an important role in the development of Indonesian education. Daar El-Qolam is an institution based on a modern pesantren system that has a principle to create a good future generation. By using their principle and implement it to all santri, it is expected that it can increase their lead. In actualizing their purpose, pesantren has created a good system both academic and non-academic. To improve their abilities, santri needs a place and chance to increase and to improve their abilities. One of the pesantren programs is to obligate all santri from class 5 to be a manager in daily activities in pesantren. The purpose of this study case is to know the relationship of self-efficacy in improving the quality of santri organization in Daar El-Qolam. The method used in research was quantitative research design that used correlational method method to know the relationship of Self-Efficacy in improving Quality of Santri Organization in Daar El-Qolam. Based on the result of research that has been done regarding the relationship of Self efficacy towards improving santri organization in Daar El-Qolam, there was the significant relationship of Self efficacy in improving quality of santri organization in Daar El-Qolam.